ADM (Dictionary of Gems and Gemology, 2009)
OBJECTIVES: Persons with opioid use disorder (OUD) are at elevated risk for engaging in the nonmedical use (NMU) of gabapentin. Despite the increased risk of respiratory depression from concomitant use of gabapentin and opioids, gabapentin is often prescribed in OUD treatment settings. This study examines the relationship between gabapentin prescribing histories and the initiation, patterns, and motivations of gabapentin NMU. METHODS: Twenty-one OUD treatment centers recruited 181 adults in 23 states reporting either past 12-month gabapentin NMU (n=150) or use only as prescribed (N=31). Cross-sectional interviews assessed demographics, substance use history/patterns, and gabapentin prescribing histories. RESULTS: Most NMU participants had a prior prescription for gabapentin (72.1%), with 45.3% having a current prescription; 27.7% had no prescription history. Diversion of gabapentin was highly prevalent for obtaining (sharing/trading=50.0%; dealer/street purchase=44.0%) and distributing gabapentin (45.3% diverted to others). Those with gabapentin NMU had higher gabapentin, but not opioid, craving scores compared with those with use as prescribed (3.8 vs. 2.2, P<0.001). Both therapeutic (84.7%) and recreational motivations (74.7%) were widely endorsed and involved high average doses (2061 mg and 2394 mg, respectively). CONCLUSIONS: Pathways to initiating gabapentin NMU among individuals with OUD are varied and include health care and nonhealth care channels. High rates of both recreational and therapeutic motivations may suggest the utility of gabapentin in potentiating opioid effects and mitigating gaps in unmet health care needs. Despite risks of concomitant use, many individuals had current prescriptions for gabapentin, highlighting the importance of screening, monitoring and risk counseling when considering gabapentin prescriptions in OUD populations.